Spent brewer’s yeast as a selective biosorbent for metal recovery from polymetallic waste streams - Sieber, Anna; Jelic, Leon Robert; Kremser, Klemens; Guebitz, Georg M. (Frontiers in Bioengineering and Biotechnology, 2024)
While the amount of electronic waste is increasing worldwide, the heterogeneity of electronic scrap makes the recycling very complicated. Hydrometallurgical methods are currently applied in e-waste recycling which tend to generate complex polymetallic solutions due to dissolution of all metal components. Although biosorption has previously been described as a viable option for metal recovery and removal from low-concentration or single-metal solutions, information about the application of selective metal biosorption from polymetallic solutions is missing. In this study, an environmentally friendly and selective biosorption approach, based on the pH-dependency of metal sorption processes is presented using spent brewer’s yeast to efficiently recover metals like aluminum, copper, zinc and nickel out of polymetallic solutions. Therefore, a design of experiment (DoE) approach was used to identify the effects of pH, metal, and biomass concentration, and optimize the biosorption efficiency for each individual metal. After process optimization with single-metal solutions, biosorption experiments with lyophilized waste yeast biomass were performed with synthetic polymetallic solutions where over 50% of aluminum at pH 3.5, over 40% of copper at pH 5.0 and over 70% of zinc at pH 7.5 could be removed. Moreover, more than 50% of copper at pH 3.5 and over 90% of zinc at pH 7.5 were recovered from a real polymetallic waste stream after leaching of printed-circuit boards. The reusability of yeast biomass was confirmed in five consecutive biosorption steps with little loss in metal recovery abilities. This proves that spent brewer’s yeast can be sustainably used to selectively recover metals from polymetallic waste streams different to previously reported studies.